1999
DOI: 10.1097/00005344-199903000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Angiotensin II Antagonism Displayed by SK-1080, a Novel Nonpeptide AT1-Receptor Antagonist

Abstract: The pharmacologic profile of SK-1080, a nonpeptide AT1-selective angiotensin-receptor antagonist, was investigated by receptor-binding studies, functional in vitro assays with rabbit and rat aorta, and in vivo experiments in pithed rats. SK-1080 inhibited the specific binding of [125I]-[Sar1, Ile8]-angiotensin II to human recombinant AT1 receptor with a 12-fold greater potency than losartan [median inhibitory concentration (IC50): 1.01 and 12.3 nM, respectively], but it did not inhibit the binding of [125I]-CG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…As a control, parallel experiments were run in the presence of either zofenopril (ZOF), an ACE inhibitor (ACEI), homogenize the form with other references or olmesartan (OLM), an AR blocker (ARB). 21 …”
Section: Introductionmentioning
confidence: 99%
“…As a control, parallel experiments were run in the presence of either zofenopril (ZOF), an ACE inhibitor (ACEI), homogenize the form with other references or olmesartan (OLM), an AR blocker (ARB). 21 …”
Section: Introductionmentioning
confidence: 99%
“…SK-1080 is structurally different from losartan and its series of imidazole analogues in having pyridylimidazole and pyridine N-oxide moieties. SK-1080 was shown to act by itself but not via its metabolites to exert a potent insurmountable antagonism [9,10] [9]. As in the binding assay, SK-1080 was shown to be significantly more potent than losartan in other experiments: over 50-fold in blocking the contractile effect of angiotensin II in rat and rabbit aorta (on the basis of calculated pK B ) and about 25-fold in blocking the pressor effect of angiotensin II in the pithed rat.…”
Section: Introductionmentioning
confidence: 90%
“…The aortic preparations were mounted for isometric force recording in an organ bath containing 20 ml of Krebs' bicarbonate buffer (mmol/l: NaCl, 118; KCl, 4.7; CaCl 2 , 2.5; NaHCO 3 , 25; MgSO 4 , 1.2; KH 2 PO 4 , 1.2; glucose, 11.0) bubbled with a mixture of gas (95% O 2 , 5% CO 2 ) and maintained at 37°C [9]. Force was measured using a force displacement transducer (Grass FT03; Grass Ins., Quincy, Mass., USA) and displayed on a chart recorder (Multicorder MC 6625; Hugo Sachs Electronic, March-Hugstetten, Germany).…”
Section: Relaxation Of Balloon-injured Carotid Arteries From Ratsmentioning
confidence: 99%
“…The difference in mean [ 18 F]fluorobenzoyl-lisinopril binding was significant between remote, noninfarct, and peri-infarct segments (P < 0.02). These preliminary data suggested that [ 18 F]fluorobenzoyl-lisinopril binds specifically to ACE, the binding is nonuniform in infarct, perinfarct, and remote noninfarct segments, and that there is apparent increased ACE activity in the juxtaposed areas of replacement fibrosis [46]. The increased ACE in the juxtaposed areas of replacement fibrosis may be a stimulus for collagen replacement and remodeling.…”
Section: F-labeled Lisinoprilmentioning
confidence: 96%